Place meaning and significance of the traditional shopping district in the city centre of Kuala Lumpur, Malaysia - Ujang, Norsidah (Directory of Open Access Journals, 2014)
Due to the rapid urbanization rate, the traditional urban environment in developing countries has been constantly replaced by modern structures with standardized images. The urban landscape of Kuala Lumpur city demonstrates a similar pattern, which, arguably, may disrupt the continuity in meaning embedded in people’s associationwith the places. This paper describes the meaning and significance of the traditional shopping districts in the city center of Kuala Lumpur, Malaysia. The researcher conducted face-to-face interviews and field observations to understand the meanings attached to the users’ experience of the traditional shopping streets located in the area. It was also to identify the urban elements that perceived to be important. The results demonstrate that the users translated various meanings of the places. The types and length of engagement, familiarity, cultural characteristics of the users and economic dependency influenced the attachment. The places are meaningful as a reflection of self and group identity thus contribute to the continuity of place identity.